Design, synthesis, and gas permeation properties of polyimides containing pendent imidazolium groups - Shrimant, Bharat; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Film-forming polymers containing ionic groups have attracted considerable attention as emerging materials for gas separation applications. The aim of this article was to synthesize new film-forming polyimides containing imidazolium groups (PI-IMs) and establish their structure-performance relationship. In this context, a new aromatic diamine, namely, N-1-(4-aminophenyl)-N-1-(4-(2-phenyl-1H-imidazol-1-yl)phenyl)benzene-1,4-diamine (ImTPADA), was synthesized and polycondensed with three aromatic dianhydrides, namely, 4,4-(hexafluoroisopropylidene)diphthalic anhydride, 4,4-(4,4-isopropylidenediphenoxy) bis(phthalic anhydride), and 4,4-oxydiphthalic anhydride to form the corresponding polyimides containing pendent 2-phenylimidazole groups (PI-IEs). Next, PI-IMs were prepared by N-quaternization of pendent 2-phenylimidazole groups present in PI-6FDA using methyl iodide followed by anion exchange with bis(trifluoromethane)sulfonimide lithium salt (LiTf2N). PI-IEs and PI-IMs exhibited reasonably high molecular weights, amorphous nature, good solubility, and could be cast into self-standing films from their DMAc solutions. Thermogravimetric analysis showed that 10% weight loss temperature of PI-IEs and PI-IMs were in the range 545-475 degrees C and 303-306 degrees C, respectively. Gas permeability analysis of films of PI-IEs and PI-IMs was investigated by variable-volume method and it was observed that incorporation of ionic groups into PI-6FDA resulted in increased permeability while maintaining selectivity. In particular, polymer bearing Tf2N- anion exhibited high CO2 permeability (33.3 Barr) and high selectivity for CO2/CH4 (41.1) and CO2/N-2 (35.4). (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1721-1729

Intrinsically microporous polyimides containing spirobisindane and phenazine units: synthesis, characterization and gas permeation properties - Shrimant, Bharat; Dangat, Yuvraj; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A - Polymer Chemistry, 2018)
A new diamine containing spirobisindane and phenazine units, namely, 3,3,3,3-tetramethyl-2,2,3,3-tetrahydro-1,1-spirobi[cyclopenta[b]phen azine]-7,7-diamine (TTSBIDA) was synthesized starting from commercially available 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethyl-1,1-spirobisindane (TTSBI). TTSBI was oxidized to 3,3,3,3-tetramethyl-2,2,3,3-tetrahydro-1,1-spirobi[indene]-5,5,6,6-tet raone (TTSBIQ) which was subsequently condensed with 4-nitro-1,2-phenylenediamine to obtain 3,3,3,3-tetramethyl-7,7-dinitro-2,2,3,3-tetrahydro-1,1-spirobi[cyclope nta[b]phenazine] (TTSBIDN). TTSBIDN was converted into TTSBIDA by reduction of the nitro groups using hydrazine hydrate in the presence of Pd/C as the catalyst. A series of new polyimides of intrinsic microporosity (PIM-PIs) were synthesized by polycondensation of TTSBIDA with commercially available aromatic dianhydrides. PIM-PIs exhibited amorphous nature, high thermal stability (T-10>480 degrees C) and intrinsic microporosity (BET surface area=59-289 m(2)/g). The gas permeation characteristics of films of selected PIM-PIs were evaluated and they exhibited appreciable gas permeability as well as high selectivity. The CO2 and O-2 permeability of PIM-PIs were in the range 185.4-39.2 and 30.6-6.2 Barrer, respectively. Notably, polyimide derived from TTSBIDA and 4,4-(hexafluoroisopropylidene)diphthalic anhydride (PIM-PI-6FDA) exhibited high CO2 and O-2 permeability of 185.4 and 30.6 Barrer with CO2/CH4 and O-2/N-2 selectivity of 43.1 and 5.1, respectively. The data of PIM-PI-6FDA for CO2/CH4 and O-2/N-2 gas pairs were located near Robeson upper bound. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 766-775
Keywords: Gas permeability; intrinsic microporosity; polyimides; spirobisindane

Spiro [fluorene-9,9 '-xanthene]-containing copolymers of intrinsic microporosity: synthesis, characterization and gas permeation properties - Shrimant, Bharat; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2018)
In the present study, a new bis(catechol) containing spiro[fluorene-9,9'-xanthene], namely, 4,4'-(spiro(fluorene9,9'-xanthene]-2',7'-diyl)bis(benzene-1,2-diol) (THSFX) was designed and synthesized. Polycondensation reactions of THSFX and varying compositions of THSFX and 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI) were carried out with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain a homopolymer and copolymers, respectively. The organo-soluble polymers exhibited reasonably high molecular weights (23300-34,100 g/mol) and could be cast into self-standing films from their chloroform solutions. X-Ray diffraction studies indicated that PIMs were amorphous in nature. These polymers exhibited high thermal stability (T-10 = 490-510 degrees C) and possessed intrinsic microporosity with high BET surface area (360-796 m(2)/g). The gas permeation properties of SFX-PIM-25 and SFX-PIM-33 were evaluated and they exhibited high gas permeability (CO2 = 3595-4034 Barrer). The gas permeability data of SFX-PIM-25 and SFX-PIM-33 was located close to 1991 Robson upper bound for CO2/N-2, CO2/CH4 and O-2/N-2 gas pairs

Synthesis, characterization, and gas permeation properties of adamantane-containing polymers of intrinsic microporosity - Shrimant, Bharat; Shaligram, Sayali V.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
A new bis(catechol) monomer, namely, 4,4-((1r,3r)-adamantane-2,2-diyl)bis(benzene-1,2diol) (THADM) was synthesized by condensation of 2-adamantanone with veratrole followed by demethylation of the formed (1r,3r)-2,2-bis(3,4 dimethoxyphenyl)adamantane. Polycondensation of THADM and various compositions of THADM and 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethylspirobisindane was performed with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain the homopolymer and copolymers. These polymers demonstrated good solubility in common organic solvents such as dichloromethane, chloroform, and tetrahydrofuran and could be cast into tough films from their chloroform solutions. GPC analysis revealed that number average molecular weights of polymers were in the range 48,100-61,700 gmol(-1), suggesting the formation of reasonably high molecular weight polymers. They possessed intrinsic microporosity with Brunauer-Emmett-Teller (BET) surface area in the range 703-741 m(2)g(-1). Thermogravimetric analysis of polymers indicated that 10% weight loss temperature was in the range 513-518 degrees C demonstrating their excellent thermal stability. THADM-based polymer of intrinsic microporosity (PIM) showed P(CO2)=1080, P(O-2)=232 and appreciable selectivity [(CO2/CH4)=22.6, (CO2/N-2)=26.7, and (O-2/N-2)= 5.7]. The gas permeability measurements revealed that with increase in the content of adamantane units in PIMs, selectivity increased and permeability decreased, following the trade-off relationship. The gas separation properties of PIMs containing adamantane units were located close to 2008 Robeson upper bound for gas pairs such as CO2/CH4, CO2/N-2, H-2/N-2, and O-2/N-2. (c) 2017 Wiley Periodicals, Inc.
Keywords: adamantane; Gas permeation; intrinsic microporosity; membranes; structure-property relations